Analysis of the Performance Efficiency of Zakat Management Institutions Using Data Envelopment Analysis: Study at LAZ Harfa Banten 2017-2020 - Arif Rohmatullah (SMART Insight, 2022)
The potential for collecting zakat in Indonesia is very high because the majority of the people are Muslims. However, the realization of zakat collection in Indonesia that has been collected by zakat management institutions, both BAZ and LAZ, is still far from the assumed amount. Zakat management institutions have an important role to collect, manage and distribute zakat. Therefore efficiency is needed by zakat management institutions in order to maximize zakat management. This study aims to analyze the level of performance efficiency of Zakat Management Institutions, especially LAZ Harfa Banten using data envelopment analysis (DEA) in the 2017-2020 period. Results of data analysis using software MaxDEA Basic 8 shows that in 2017 and 2020 LAZ Harfa Banten experienced perfect efficiency with a score of 100% or had an efficiency score of 1. Meanwhile in 2018 and 2019 LAZ Harfa Banten experienced inefficiency, namely in 2018 with an efficiency score of 94.94% and in 2019 the efficiency value was 83.56%. Inefficiency occurs because the input variable whose actual value is not in accordance with the DEA calculation target, namely total assets. Meanwhile, the output variables, namely the amount of zakat receipts and the amount of zakat distribution, both experience inefficiency because the actual value and target value are not appropriate or balanced.